Desenvolvimento de índices de preços para infraestrutura no Brasil - Monsanto, Bruno (2015)
This work presents a set of infrastructure price indices, developed with the purpose of providing specific indicators for this sector in Brazil. A survey of the major indices of this nature produced in Brazil and worldwide was held. The main international references were the Organization's for Economic Cooperation and Development - OECD and the European Union member countries. From this analysis, we identified three key issues for the development of work: i) what is the set of infrastructure works to be represented by the indexes and how to delimit this set?; ii) price indexes currently produced in Brazil represent part of this set?; iii) how to develop a set of indices, built on the same methodological basis, nationwide, able to adequately represent this body of work? As a result of work, a set of ten price indices of infrastructure was created built on the same methodological basis, nationwide and offers a range of infrastructure works, whose definition was one of working objects. In addition to the methodological basis for construction of the indices were calculated their respective historical series for the period December / 2000 (base = 100) to February / 2015, from which the indices are analyzed in several ways, for example, through comparative analysis of the ten indices between them and analysis of the behavior of the indices over time, considering the economic context by observing selected indicators.